ANALISIS PENGARUH KOMPENSASI, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA DOSEN UNIVERSITAS PUTRA INDONESIA YPTK PADANG - Mulyani, Sitti Rizki (Jurnal Ekobistek, 2016)
As for the purpose of study was determine the effect of compensation,discpline and commitment to the organization?s performance YPTK lecturer at the University Putra Indonesia Padang This research was conducted wirhin the University Putra Indonesia Padang YPTK population in this study was the entire faculty within the University Putra Indonesia YPTK . The samples were 50 people with engineering porposional types and sources of research data consist of primary data is data obtained from the respondents throught questionnairs opinion research and secondary data is data obtained from Universitas Putra Indonesia YPTK data analysis techniques used in the study is hypothesis testing linear regression analysis using SPSS version 17.0. The results  found 1) compensation positiveand significant effect on the performance YPTK lecturer at theUniversity Putra Indonesia Padang, 2) Discipilne of work but not significant positive effect on performance YPTK lecturer at the University Putra Indonesia Padang, 3)Organizational Commitment positive and significant impact on the performance of University lecturers Putra Indonesia Padang YPTK, 4) Compensation, Disciplin and commitment to work together organizations  have a significant effect on the performance of university lecturers Putra Indonesia Padang YPTK donation effect by 46% nd remaining 54% is influenced by other factors not included in the scope of this study finally, the author suggest to University Putra Indonesia Padang YPTK order to continue to improve compensation, and commitment to maintain discipline work, so that faculty performance continues to increase and produce graduates who are qualified. Keywords :       Compensation, Work Discipline, Organizational Commitment , Performance  Lecturer.